Interactive Internet Inter Bank Service System for Saving Account - Cha, Cheng Yee (2001)
The purpose of this project is to develop a prototype Internet Inter Bank System that allowing customer to perform transactions inter bank through a one stop web site. The transaction services provided by ths prototype system include account enquiry, fund transfer and bill payment. The transaction services are applicable for only saving account. This project uses development methodology called Web Page Development Methodology (WPD). Finally, this project discusses some problems, constraints and recommendations for future development.